The Development of Food and Nutrition Security Index at Provincial Level in Indonesia - Gantina, Anggit; Martianto, Drajat; Sukandar, Dadang (Jurnal Gizi dan Pangan, 2020)
This study aimed to develop a novel Food and Nutrition Security (FNS) index to be implemented at provincial level in Indonesia. Principal component analysis was used to calculate food and nutrition security index based on 23 indicators, data were obtained from provincial and national public report published in 2010 and 2013. These indicators were further grouped into three different dimension of food availability, food accessibility and food utilization. Principal Component Analysis (PCA) was then used to calculate each aspect and the FNS indices. The index was later used to categorize food and nutrition security performance of a region into one of three levels, namely secure, vulnerable or insecure. The application of this new FNS index found that most of Indonesia’s regions (87.5%) were categorized as vulnerable (50.0%) and insecure (37.5%) and only 12.5% had high food and nutrition security performances in 2013. Among all provinces, Bali had the best performance in 2013, while East Nusa Tenggara had the lowest performance in 2010 and 2013. In 2013, the food availability status of all the provinces were categorized as secure. However, their status on food accessibility and food utilization showed many of them fell into vulnerable and insecure categories. Hence, the effort to increase the national food and nutrition security performance should focus on improving food accessibility and food utilization.